2006
DOI: 10.1128/iai.00363-06
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Avian PathogenicEscherichia coliPlasmids by a CommensalE. coliIsolate Enhances Its Abilities To Kill Chicken Embryos, Grow in Human Urine, and Colonize the Murine Kidney

Abstract: We have found an avian pathogenic Escherichia coli (APEC) plasmid, pAPEC-O2-ColV, which contains many of the genes associated with APEC virulence and also shows similarity in content to a plasmid and pathogenicity island of human uropathogenic E. coli (UPEC). To test the possible role of this plasmid in virulence, it was transferred by conjugation along with a large R plasmid, pAPEC-O2-R, into a commensal avian E. coli strain. The transconjugant was compared to recipient strain NC, UPEC strain HE300, and donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
128
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(138 citation statements)
references
References 52 publications
7
128
1
2
Order By: Relevance
“…Isolados APEC também podem representar risco zoonótico para seres humanos, devido à presença, nos mesmos, de genes de virulência encontrados em E.coli patogênicas (causadoras de infecção do trato urinário e meningite em recém-nascidos) para seres humanos (Skyberg et al 2006).…”
Section: Discussionunclassified
“…Isolados APEC também podem representar risco zoonótico para seres humanos, devido à presença, nos mesmos, de genes de virulência encontrados em E.coli patogênicas (causadoras de infecção do trato urinário e meningite em recém-nascidos) para seres humanos (Skyberg et al 2006).…”
Section: Discussionunclassified
“…Transformation of an avirulent wild-type E. coli strain with a recombinant plasmid (pHK11) encoding for colicin V led to increased colonization of the chicken trachea (Wooley et al, 1998). Recently, transferring 2 APEC plasmids (ColV and large R) into a commensal E. coli strain by conjugation enhanced its abilities to kill chicken embryos, grow in human urine and colonize the murine kidney (Skyberg et al, 2006). Based on a selection of common traits that include plasmid-borne traits, two multiplex polymerase chain reaction (PCR) protocols have recently been described for the identification of APEC Ewers et al, 2005).…”
Section: The Apec Pathotypementioning
confidence: 99%
“…Recently, these genes have been mapped to a conserved region of a 93 kb cluster of putative virulence genes on a ColV plasmid, pAPEC-O2-ColV . Transforming an avian commensal E. coli strain with this plasmid led to a significant increase in the strain's lethality for chicken embryos and ability to colonize the murine kidney (Skyberg et al, 2006). Besides aerobactin, other iron acquisition and transport systems carried on the ColV plasmid include the salmochelin siderophore system (encoded by the iroBC-DEN locus), sitABC iron transport systems and a putative iron transport system novel to APEC (eit) .…”
Section: Progress Towards Unravelling Apec Virulence Factorsmentioning
confidence: 99%
“…Johnson et al (19,22) showed that iss occurs on a conserved virulence cluster found on conjugative ColV and ColBM plasmids of APEC isolates. Skyberg et al (42) found that transfer of these virulence plasmids to commensal E. coli increased the recipient strains' ability to grow in human urine and to colonize the kidney of mice. In order to follow up on this observation, Johnson et al (20) sequenced the entire genome of APEC O1 (an O1:K1:H7 strain) and compared it to other known E. coli genomes.…”
Section: Discussionmentioning
confidence: 99%